2016
DOI: 10.1042/bcj20160581
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding protein IQGAP1: an insulin-dependent link between caveolae and the cytoskeleton in primary human adipocytes?

Abstract: The ubiquitously expressed IQ motif-containing GTPase activating protein-1 (IQGAP1) is a scaffolding protein implicated in an array of cellular functions, in particular by binding to cytoskeletal elements and signaling proteins. A role of IQGAP1 in adipocytes has not been reported. We therefore investigated the cellular IQGAP1 interactome in primary human adipocytes. Immunoprecipitation and quantitative mass spectrometry identified caveolae and caveolae-associated proteins as the major IQGAP1 interactors along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
7
2
Order By: Relevance
“…Caveolins are a family of integral membrane proteins that constitute the principal components of caveolae membranes and are involved in receptor‐independent endocytosis . The IQGAP1 colocalization with the prescribed caveolae marker protein, caveolin‐1, has been established by confocal microscopy and proximity assay . Yamaga et al (2004) reported that p122RhoGAP/DLC‐1 binds caveolin‐1 through the RhoGAP domain, and that the START domain could bind to cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caveolins are a family of integral membrane proteins that constitute the principal components of caveolae membranes and are involved in receptor‐independent endocytosis . The IQGAP1 colocalization with the prescribed caveolae marker protein, caveolin‐1, has been established by confocal microscopy and proximity assay . Yamaga et al (2004) reported that p122RhoGAP/DLC‐1 binds caveolin‐1 through the RhoGAP domain, and that the START domain could bind to cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] The IQGAP1 colocalization with the prescribed caveolae marker protein, caveolin-1, has been established by confocal microscopy and proximity assay. 44 Yamaga et al (2004) reported that p122RhoGAP/DLC-1 binds caveolin-1 through the RhoGAP domain, and that the START domain could bind to cholesterol. Furthermore, in PC12 cells, the agonist-induced primary increase in Ca 2+ recruits PLC-δ1 into lipid rafts from other parts of the PM or the CY by other scaffold proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others previously reported that IQGAP1 also interacts with receptor tyrosine kinases including VEGF receptor type 2 in endothelial cells and PDGF receptor in VSMC to couple receptor tyrosine kinases signal to enhance migratory responses (18,50). Of note, IQGAP1 is localized at caveolae/ lipid rafts in primary human adipocytes and VSMCs (14,18).…”
Section: Introductionmentioning
confidence: 63%
“…Caveolins are a family of integral membrane proteins that constitute the principal components of caveolae membranes and are involved in receptor-independent endocytosis (Scherer et al, 1996, Tang et al, 1996, Williams et al, 2004). The IQGAP1 colocalization with the prescribed caveolae marker protein, caveolin-1, has been established by confocal microscopy and proximity assay (Jufvas et al, 2016). Yamaga et al (2004) reported that p122RhoGAP/DLC-1 binds caveolin-1 through the RhoGAP domain, and that the START domain could bind to cholesterol.…”
Section: Discussionmentioning
confidence: 99%